HMFcalc: An online tool for calculating dark matter halo mass functions - Murray, Steven; Power, C.; Robotham, A. (2013)
The dark matter halo mass function (HMF) is a characteristic property of cosmological structure formation models, quantifying the number density of dark matter haloes per unit mass in the Universe. A key goal of current and planned large galaxy surveys is to measure the HMF and to use it to test theories of dark matter and dark energy. We present a new web application for calculating the HMF-the frontend HMFcalc and the engine hmf. HMFcalc has been designed to be flexible, efficient and easy to use, providing observational and theoretical astronomers alike with the means to explore standard functional forms of the HMF or to tailor their own. We outline the theoretical background needed to compute the HMF, we show how it has been implemented in hmf, and finally we provide worked examples that illustrate HMFcalc's versatility as an analysis tool. © 2013 Elsevier B.V.